When language is maladaptive: recommendations for discussing self-injury. Issue 2 (18th June 2019) - Hasking, Penelope; Lewis, Stephen P.; Boyes, Mark E.
Abstract : Purpose: The purpose of this paper is to call on researchers and clinicians to carefully consider the terminology used when discussing non-suicidal self-injury (NSSI), and specifically the use of the term "maladaptive" coping. Design/methodology/approach: Drawing on literature regarding stigma, language and self-injury to support the argument that the term maladaptive is inappropriate to describe self-injury. Findings: Use of the term maladaptive conflates short-term effectiveness with long-term outcomes and ignores context in which the behaviour occurs. Social implications: Use of the term maladaptive to describe self-injury can invalidate the person with a history of NSSI, impacting stigma and potentially help-seeking. An alternate framing focussed on specific coping strategies is offered. Originality/value: Language is a powerful medium of communication that has significant influence in how society shapes ideas around mental health. In proposing a change in the way the authors' talk about self-injury there is potential to significantly improve the wellbeing of people with lived experience of self-injury.